Anatomical variations of the superficial palmar arch and its clinical relevance - Mališ, Miloš; Kapor, Slobodan; Puškaš, Laslo; Aksić, Milan; Blagojević, Valentina; Žarković, Nikola; Djurašić, Ljubomir; Filipović, Branislav; Vukomanović Djurdjević, Biserka (Vojnosanitetski pregled, 2022)
Background/Aim. In-depth knowledge of the vascular network of the hand is of great importance in modern medicine. The main vessel of the hand is the superficial palmar arch (SPA). As typically described in anatomical textbooks, it arises as a terminal branch of the ulnar artery, which then anastomoses with the superficial palmar branch of the radial artery. However, the SPA is characterized by remarkable variability, which has been the area of interest of many researchers so far. The aim of this study was to exert a comprehensive examination of the anatomy of the SPA. Methods. The research was conducted at the Institute of Anatomy “Niko Miljanić” on a total number of 14 cadavers. After careful dissection, variations of the modality of formation of the SPA and its distance of the SPA from Kaplan’s cardinal line were observed on the right hands. Collected data were then analyzed statistically in SPSS 11.0 using the Mann-Whitney U test, with the accepted level of statistical significance of p < 0.05. Results. According to Coleman and Anson’s classification, the higher incidence of the incomplete type (57.14%) of the SPA was observed compared to the complete type (42.86%). In addition to this, a statistically significant difference was discovered in the distance of the SPA from Kaplan’s cardinal line between two groups with complete and incomplete types, respectively. The parameter examined in the group with the complete type took the value of 2.13 ± 0.32 cm, while in the group with the incomplete type measured 3.33 ± 0.87 cm. Conclusion. The present study showed a very important complexity in the domain of anatomy of the SPA with numerous clinical implications. For that reason, a thorough evaluation of the hand circulatory system should be considered while planning surgical procedures in order to avoid operative and postoperative complications.